Microfinance of Women Entrepreneurship in Alleviating Poverty - Nik Syuhailah Nik Hussin; Zuraimi Abdul Aziz; Mohd Rafi Yaacob; Nur Sha Azelda Hashim; Nik Madeeha Nik Mohd Munir; Siti Fariha Muhamad (2015)
Microfinance has shown to be an effective tool for combating poverty, creating jobs, and improving the poor peoples. Poverty alleviation is the main objective of improving the socioeconomic. It has becomes main targets and attention at many developing and developed countries. The objective of this research is to find out the contributing factors in alleviating poverty for women entrepreneurship. A total of 97 samples were collected from women entrepreneurship in Terengganu. Data analyses were conducted using SPSS 20.0.